Resilience and workability among breast cancer survivors (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2019)
Breast cancer is the most common neoplasia in women worldwide. Medical advances in prognosis and treatments have improved survival rates, however, many women report physical and psychological problems derived from the impact and the administered treatments that can undermine breast cancer survivors’ workability. Given that breast cancer occurs at working age (35-65 years) and due to the importance that work has in their recovery process, it is crucial to determine the psychological resources that breast cancer survivors may use to reestablish their ability to work. In this sense, resilience understood as the ability to successfully adapt in the face of stress and adversity may play an important role. Hence, the aim of this study is to explore resilience levels in breast cancer survivors and to study its relationship with workability. The sample was comprised of 44 breast cancer survivors of Spain, with a mean age of 51.93 (SD = 8.77). Participants completed the Wagnild and Young Resilience Scale (Spanish version adapted by Novella, 2002) and Work Ability Index (WAI, Tuomi et al., 1997).The results of the descriptive statistics revealed that breast cancer survivors displayed high levels of resilience. Moreover, the results of the Pearson correlation indicated that there was a significant positive association between global resilience and workability (r = .33, p = .03), as well as between the dimensions self-confidence (r = .37, p = .01) and personal satisfaction (r = .33, p = .03). Age did not correlate with resilience nor with workability. Thus, identifying the factors that positively influence breast cancer survivors’ adjustment to working life can help to develop interventions with the aim to restore working ability in this population. Besides, given the importance that return-to-work have in this population, this research may contribute to expanding knowledge regarding the recovery process in breast cancer survivors.